Robot-assisted Müllerian compartment resection for cervical cancer - Li, Ya; Na, Jing; Wang, Xinyou (Frontiers in Oncology, 2024)
ObjectiveRadical hysterectomy has been established as the standard treatment for early stage cervical cancers. Despite numerous efforts to standardize the technique for radical hysterectomy across varying extents of tumor invasion, success has been inconsistent. Total Müllerian Compartment Resection (TMCR), an ontogenetic compartment-based oncologic surgery initially developed for open procedures by Professor Höckel, offers a standardized approach applicable to all patients with locally confined tumors. This method holds promise for achieving thorough oncologic clearance while maintaining acceptable complication rates. Moreover, robotic-assisted surgery may further reduce morbidity compared to open surgery. In this context, we provide a detailed step-by-step description of robotically assisted Total Müllerian Compartment resection (R-TMCR) for cervical cancer and present feasibility data from a cohort of 20 patients.Subjects and methods20 patients with stage IA1-IB2 cervical cancer, robot-assisted resection of the Müllerian embryonic compartment was undertaken. Key metrics such as operative duration, intraoperative blood loss, and postoperative complication rates were meticulously recorded and analyzed.ResultsThe duration of the surgery varied from 185 to 500 minutes, with intraoperative blood loss ranging between 5 mL and 300 mL. Postoperative hemoglobin levels dropped by -15 to 40 g/L from their preoperative values. Notably, there were no instances necessitating conversion to open surgery, and no intraoperative complications occurred. The rate of postoperative complications was 0%. Over the follow-up period, which averaged 18 months, there were no observed locoregional recurrences of cervical cancer, nor were there any deaths attributed to cervical cancer during this time.ConclusionThe application of robotic Müllerian compartment resection in the surgical treatment of cervical cancer is both safe and feasible. Utilizing robotic technology enables more precise and refined surgical outcomes. Combining embryonic compartment-based radical hysterectomy with the principles of membrane anatomy can standardize and optimize the surgical process, helping surgeons master radical hysterectomy more quickly and effectively.